PERAN INDUSTRI KOMIK SUPERHERO BAGI DIPLOMASI PUBLIK AMERIKA SERIKAT - Aji, Prasetyo Hingkawono; Damayanti, Christy; Dipokusumo, GPH (Solidaritas, 2020)
This research analyzes and seeks the role of the US superhero industry for US public diplomacy. The comic industry is one of the industries and popular culture in the United States that continues to increase from year to year, up to the modern era like now. The role of the United States government in utilizing the superhero comic industry as a tool of public diplomacy made the comic industry make a big impression in conveying the good image of the United States. This research was examined using the theory of public diplomacy and mass media collected in public diplomacy. This research discusses the superhero comic industry and aims to study its role in US public diplomacy. The method used in this research is descriptive qualitative research method with secondary data sources. From this study, the authors found research in the United States involved in the superhero comics industry in carrying out public diplomacy. Because of the nature and characteristics of superhero comics that are very easily accepted by the international community, the United States government requires public diplomacy. Keywords: Superhero comic industry, United States Government, Public Diplomacy